English Pre-Service Teachers’ Voice: Game Based Learning to Increase Students’ Learning Engagement - Hasibuan, Anjani Vicka Prasasti (Department of English Language Education, UIN Sunan Ampel Surabaya, 2023)
In integrating technology in language learning can be done through various way, one of them through game based learning. The game which used in the language learning, especially English class can be used to increase students’ learning engagement. Since English is a foreign language in Indonesia, students need learning engagement in order to understand the material easily. However, in implementing game based learning, teacher need to consider the appropriate game based learning tool, especially pre-service teacher in their first teaching practice. The research used descriptive qualitative to describe how English pre-service teachers implement game based learning to increase students’ learning engagement and how students’ learning engagement is increased through game based learning through questionnaire. The subject was English pre-service teacher in one of state university in Surabaya. The result showed English pre-service teachers implemented game based learning at the first meeting, as main activity, and as assessment in order to increase students’ learning engagement. Furthermore, students’ learning engagement increased through the way they used the game. Keywords: English Pre-Service Teacher, Game Based Learning, Students’ Learning Engagement